Emergência do polo moveleiro de Linhares e políticas para o setor no Espírito Santo (1960-1995) - Guedes, Paulo Cezar Pinheiro (2008)
A history of furniture making in Espírito Santo, with reference to the contribution of the Italian immigrants, represented through their ability and culture in the making of handcraft furniture, while simultaneously developing their coffee plantations, thus maintaining the characteristics of family-group work for their sustenance. We herein consider the effects of lumber exploration and its scarcity in Espírito Santo, as welll as the displacement of the population from the South of Espírito Santo upwards to the region of Linhares and environs, as well as its relationship to the appropriation and exploration of land and lumber resourses, which includes the establishment of familly lumber mills and woodwork shops. It also deals with the transformation of this reality, due to the advent of new technologies, market competitiveness, and models of management in the creation of the Linhares Furniture Pole, which includes references to the substitution of raw materials in natura, for MDF and its marketing aspects, both in terms of its popularization, as well as in terms of the quality of the product. The study finally includes considerations on the creation of employment within the furniture manufacturing and business complex.